ONBOARD COMPUTER AND MISSION CONTROL (CAHIERS MAGELLANES-NS, 2024)
In our dynamic technological landscape, this research focuses on the development and integration of a versatile Onboard Computer and Ground Control Software (GCS) system. The Onboard Computer, driven by autonomous flight software, collects sensor data and makes real-time decisions, serving as the mission's core. It transmits telemetry data to the GCS, facilitating real-time monitoring. The GCS, acting as the central control hub, receives data and sends commands, establishing bidirectional communication for efficient mission management. Emphasizing adaptability, these systems offer scalable solutions for diverse projects, bridging the gap between data collection and mission control.